Enxágue bucal com carboidratos e o desempenho de triatletas no ciclismo - Evelyn Suene Maia de Assis (2022)
Objective: to investigate the acute effect of carbohydrate mouth rinse about the cycling performance in triathletes. Methods: Participated 13 male triathlon athletes (29,6 ± 7,8 years), with the avarage maximium VO2 of 51,33 ± 6,04 ml.kg-1.min-1, with the avarage total body mass 73,29 ± 7,1 kg, fat percentage 12,50 ± 5,4%, and average stature 1,75 ± 0,64 meters. The athletes were underwent to a test protocol of performance time trial in cycling, in which they did 40 kilometers in the shortest possible time, in a stationary way, on their own bicycles. Previously to the time trial test, the volunteers did 1,5 km of swimming in an Olympic-sized swimming pool. In the time trial test in cycling, the athletes were submitted to two experimental conditions, with an interval of 7 days. In each condition, they received a bolus of 25 ml of maltodextrin diluted in water, with a concentration of 16% (ExCHO), or 25 ml of placebo, containing 0% of carbohydrate (ExPLA). The volunteers performed the mouth rinse with the provided drinks, eliminating them later. The mouth rinse was performed every 12,5% of the total distance to be done. The subjective perception of effort (RPE) was recorded throughout the test, in the fifth kilometer traveled (5km moment) and at the end of the distance (40km moment) covered in the test. The capillary lactate was collected before swimming, before and after the time trial test. The blood glucose was collected before and after the test. Results: between the experimental conditions, in the time trial test, there were no significant differences in the duration variables (ExPLA: 73min42s ± 4min43s; ExCHO: 73min55s ± 4min51s; p = 0,600; d = 0,04), relative power to total body mass pre-exertion (watts/kg) (ExPLA: 2,61 ± 0,39; ExCHO: 2.61 ± 0,40; p = 0,90; d = 0,01) and relative power post-exertion total body mass (watts/kg) (ExPLA: 2,64 ± 0.40; ExCHO: 2.65 ± 0,40; p = 0,93; d = 0,01). Also, there was no significant difference (p = 0,70; d = 0,08) in mean RPE in ExPLA (5,41 ± 0,99) and ExCHO (5,50 ± 1,22) conditions. For data on avarage lactate concentrations (mmol/L) pre swimming (ExPLA: 2,52 ± 0,15; ExCHO: 2,30 ± 0,13; p = 0,186; d = 1,56), pre cycling ( ExPLA: 4,94 ± 0,57; ExCHO: 4,61 ± 0,51; p = 0,276; d = 0,6) and post cycling (ExPLA: 5,38 ± 0,88; ExCHO: 5,76 ± 0,88 1.23; p = 0,685; d = 0,35), there was no statistics significant difference between the experimental conditions. Regarding the average blood glucose (mg/dL), the pre cycling moments (ExPLA: 92,00 ± 2,01; ExCHO: 95,53 ± 3,35; p = 0,315; d = 1,27) and post-cycling (ExPLA: 89,69 ± 2,14; 91,61 ± 1,85; p = 0,475; d = 1,01), also showed no significant difference between the experimental conditions. There was no significant difference in average FC (bpm) (p = 0,422; d = 0,09) between ExPLA (148 ± 11,51) and ExCHO (149 ± 10,78) conditions. Conclusion: The mouth rinse with carbohydrates does not promote improve in the physical performance and the psychobiological parameters, in addition to different physiological responses, in triathletes, in cycling.